Challenges and Problems in Restricting the Expansion of Women Entrepreneurship in India: Examining the Barriers Faced by Women Entrepreneurs in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Entrepreneurship refers to the act of setting up a new business or reviving an existing business so as to take advantages from new opportunities. Last five decades have seen phenomenal changes in the status of women in India. According to NSSO 6th Economic census, only 14 of business establishments in the country are being run by women entrepreneurs. Indian women do 9.8 times care work than Indian men do. Women in India face many problems to get ahead their life in business. They face difficulty due to specific women problems in India, arising due to old traditions, socio cultural norms, male dominant society, family responsibilities, Indian values and ethics. This paper focuses on challenges and problems that are resulting in restricting the expansion of women entrepreneurship in India.